Pendidikan Islam Sebagai Grand Design Pendidikan Karakter - Muhammad Isnaini (LPPM IAIN Sorong, 2015)
Character education is a positive offer in the eradication of moral crises which particularly emerged in our students. Therefore, the internalization of values of character education in the educational institution is a must. As an Islamic education institution in Indonesia, the existence of Boarding school is considered to be able to develop values of character education which may be done through formal or non-formal curriculum. This is so because since its early existence, Boarding school has delineated its distinctive feature which is different from the other common types of education. Here, the implementation of character values have been integrated (within large portion) in the religious subjects. Character education, at least in the discourse, still a potent tool in addressing the arious issues that whack this nation. Not only in Indonesia, even in developed countries such as the United States, Germany, Japan, and, still rely on character education as a mainstay of kick to overcome various moral issues at hand. Character education became very warm issue in the education scene in Indonesia due to the rampant cases of moral that afflicts this nation, ranging from scenes in high State institutions, educational nstitutions until those cases that occur in the streets. The cases allegedly due to the failure of education that has lasted until today. Criticisms of the educational world tends to be mechanical, cognitive aspects than prefer the affective and psychomotor, and a series of spicy criticism more have graced the writings of educational expert. In order to respond to these concerns, the Government now, through the Ministry of education and culture and supported by the Ministry of Religion, raised character education agenda as the national education agenda. Sayang sayang thousand, until now there has been no clear concept of philosophy as well as on the technical implementation. This paper will offer solutions to various problems in philosophy as well as the implementation of character education. The author of the theme of humanist-religious is one of spirits in character education. The reason is that to improve the character of a nation, certainly could not depart from values which do not come from the nation itself. Humanist-religious is a character that belongs to the people of Indonesia so that character education is applied in this country inevitably had to depart from this character. After discussing the philosophy of character education from the perspective of humanist-religious, the author offers some alternatives that are related to the stages of education, learning methods, as well as the position of teachers in character education